2015
DOI: 10.1002/ajh.23947
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival of cancers among 1,054 hemophilia patients: A nationwide and 14‐year cohort study

Abstract: As life expectancy increases in persons with hemophilia (PWH), more age-related diseases such as cancer emerge among this patient group. The aim of this study was to investigate incidence and survival of cancers among PWH in Taiwan. We analyzed data of 1,054 PWH retrieved from Taiwan's National Health Insurance Research Database between 1997 and 2010, by comparing variables to 10540 age-and gendermatched healthy individuals from the general population. There were 43 PWH and 178 individuals of general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…For other pdFVIII products, similar data have been reported: loading 2 Case Reports in Hematology doses ranged from 25-200 IU/kg, mean doses per ED were 50-70 IU/kg, and treatment for up to 10 days was common [6][7][8][9]. An increased incidence of haematologic malignancies and other cancer types among patients with haemophilia compared with matched controls has been reported in several longitudinal studies [10,11]. Close follow-up for malignancies in these patients is therefore recommended [11].…”
Section: Discussionsupporting
confidence: 66%
“…For other pdFVIII products, similar data have been reported: loading 2 Case Reports in Hematology doses ranged from 25-200 IU/kg, mean doses per ED were 50-70 IU/kg, and treatment for up to 10 days was common [6][7][8][9]. An increased incidence of haematologic malignancies and other cancer types among patients with haemophilia compared with matched controls has been reported in several longitudinal studies [10,11]. Close follow-up for malignancies in these patients is therefore recommended [11].…”
Section: Discussionsupporting
confidence: 66%
“…The incidence of malignancies in patients with hemophilia is higher, compared with general population, but most patients have virus-related cancers (22)(23)(24), because prevalence of hepatitis B, C and human immunodeficiency virus infection is higher, compared with the general population (23). Thus, hepatocellular carcinoma, leukemia and lymphoma are the most frequent types of cancers in patients with hemophilia (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery of malignant tumors in patients with hemophilia is associated with increased risk of postoperative complications, including bleeding, despite proper replacement therapy (27). Nevertheless, it appears that associated hemophilia does not have a detrimental effect on long-term prognosis of treated malignancies (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxis and early treatment with FVIII concentrate that is safe from viral contamination have dramatically improved the prognosis of patients with severe hemophilia. Nevertheless, approximately one quarter of patients with severe hemo- 46 showed that among six PWH with leukemia, four had acute lymphoblastic leukemia and two had acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%